ESport programs in high school: what’s at play? - Lemay, Antoine; Dufour, Magali; Goyette, Mathieu; Berbiche, Djamal (Frontiers in Psychiatry, 2024)
A growing number of high schools in Canada offer eSports (ES) in their facilities, which raises concerns regarding this activity's potential health risks for adolescents. The aim of this study is to describe the characteristics of 67 adolescent ES players (ESp) and to compare them to 109 recreational gamers in their high school (nESp). The two groups were compared on (1) sociodemographic and academic characteristics; (2) online and offline activities; (3) psychological characteristics. Results show that ESp spend more time on online activities and report a higher proportion of problematic gaming compared to the nESp group. ESp report more often that gaming has positive consequences on their physical health and report more often negative consequences on their education compared to the nESp group. These results underscore the importance of screening gaming problems among adolescent ES players.Targeted prevention should be carried out with these teenagers and in order to be adapted, prevention efforts should consider both, the positive and negative consequences that ESp experience from gaming.